2023
DOI: 10.1186/s13054-023-04525-3
|View full text |Cite
|
Sign up to set email alerts
|

Early plasma angiopoietin-2 is prognostic for ARDS and mortality among critically ill patients with sepsis

Abstract: Angiopoietin-2 (Ang-2) is associated with vascular endothelial injury and permeability in the acute respiratory distress syndrome (ARDS) and sepsis. Elevated circulating Ang-2 levels may identify critically ill patients with distinct pathobiology amenable to targeted therapy. We hypothesized that plasma Ang-2 measured shortly after hospitalization among patients with sepsis would be associated with the development of ARDS and poor clinical outcomes. To test this hypothesis, we measured plasma Ang-2 in a cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…Interestingly, values of IL-6 are 10 to 200-fold higher in “hyperinflammatory” ARDS when compared to severe COVID-19 ARDS [ 42 ]. Ang-2, another marker and mediator of vascular endothelial activation, is elevated in patients with both ARDS and sepsis and is associated with severity of illness in sepsis, development of ARDS in sepsis, and higher mortality [ 43 ]. Other plasma biomarkers consistently associated with ARDS mortality include IL-8, intracellular adhesion molecule 1, thrombomodulin, plasminogen activator inhibitor 1 (PAI-1), and protein C (lower).…”
Section: Biological Subphenotypesmentioning
confidence: 99%
“…Interestingly, values of IL-6 are 10 to 200-fold higher in “hyperinflammatory” ARDS when compared to severe COVID-19 ARDS [ 42 ]. Ang-2, another marker and mediator of vascular endothelial activation, is elevated in patients with both ARDS and sepsis and is associated with severity of illness in sepsis, development of ARDS in sepsis, and higher mortality [ 43 ]. Other plasma biomarkers consistently associated with ARDS mortality include IL-8, intracellular adhesion molecule 1, thrombomodulin, plasminogen activator inhibitor 1 (PAI-1), and protein C (lower).…”
Section: Biological Subphenotypesmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that genetic variations in the Ang-2 gene can alter its expression ( 80 ). The plasma level of Ang-2 can serve as a reliable prognostic and mortality predictor for patients with sepsis and ARDS ( 81 ). Genetic polymorphisms contributing to ARDS occurrence are generally relevant to innate immunity, surfactant function, oxidative stress, and capillary endothelium ( 71 ).…”
Section: Ards Heterogeneitymentioning
confidence: 99%
“…A systemic review and meta-analysis of 18 pertinent studies and 27 datasets revealed that Ang-2 has potential diagnostic and prognostic capabilities regarding ARDS, especially among Chinese people [55]. Multivariable models from a cohort of 757 patients with sepsis showed that Ang-2 was linked to the development of ARDS and 30-day mortality, making it a promising biomarker and an attractive target for vascular injury [56]. It has been highlighted that the ACE2/Ang-(1-7)/MasR axis is a major component in the development of pulmonary fibrosis in ARDS [57].…”
Section: Endothelial Injury Biomarkersmentioning
confidence: 99%